2015
DOI: 10.1002/sdr.1539
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical knowledge is related to understanding stocks and flows: results from two nations

Abstract: Stocks and flows (SF) are essential to every-day judgments: debt changes with rates of incomes and expenses, and body weight with calories consumed and energy expended. Research suggests that individuals with strong mathematical skills have a poor understanding of SF. However, past research used homogeneous participant samples and the relationship between mathematical knowledge and performance in SF tasks was not tested. In two studies involving different populations from China and the U.S.A, we find that indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…We found that the male respondents performed better than the female respondents in a number of tasks, both on the (in)correct outcome measure and the correlation heuristic measure. Gender differences have been found in varying degrees in other studies (Booth Sweeney and Sterman, ; Sterman, ; Abdel‐Hamid et al ., ; Baghaei Lakeh and Ghaffarzadegan, ; Qi and Gonzalez, ). Our study strengthens the evidence that a gender difference indeed exists in STI tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the male respondents performed better than the female respondents in a number of tasks, both on the (in)correct outcome measure and the correlation heuristic measure. Gender differences have been found in varying degrees in other studies (Booth Sweeney and Sterman, ; Sterman, ; Abdel‐Hamid et al ., ; Baghaei Lakeh and Ghaffarzadegan, ; Qi and Gonzalez, ). Our study strengthens the evidence that a gender difference indeed exists in STI tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Similar, if the net flow is negative the level of the stock decreases. Throughout the past decade, numerous studies have shown that people experience difficulties solving problems that involve accumulation (Booth Sweeney and Sterman, ; Pala and Vennix, ; Cronin et al ., ; Sterman, ; Abdel‐Hamid et al ., ; Korzilius et al ., ; Baghaei Lakeh and Ghaffarzadegan, ; Fischer and Gonzalez, ; Qi and Gonzalez, ; Weinhardt et al ., ). The flow of materials in and out of a stock is present in all facets of life; it determines what your bank statement looks like at the end of the month or whether you overfill your coffee cup in the morning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attention of many system dynamics researchers has turned to the “stock‐and‐flow error” (SFE), which deals with the apparent difficulties humans have to infer the behavior of stock variables from information about the flows adding to or draining stocks (Baghaei Lakeh & Ghaffarzadegan, ; Bleijenbergh, Vennix, Jacobs, & van Engen, ; Booth Sweeney & Sterman, , ; Capelo & Dias, ; Cronin & Gonzalez, ; Cronin, Gonzalez, & Sterman, ; Qi & Gonzalez, ; Sterman, ; Stouten & Größler, ; Stouten, Heene, Gellynck, & Polet, ; Sweeney & Sterman, ; Sweeney & Sterman, ; Sweeny & Sterman, ). Just like the MoF thread, this line of research investigates decision processes and suggests that pattern‐matching heuristics may be responsible for the difficulty to intuitively understand accumulation.…”
Section: Mental Models In Different Strands Of Management Research LImentioning
confidence: 99%
“…Several studies have shown that people have difficulty inferring the behavior of a stock variable based on information about its inflows and outflows (Booth Sweeney and Sterman, ; Kapmeier, ; Cronin et al , ; Sterman, ; Abdel‐Hamid et al ., ; Qi and Gonzalez, ). However, little progress has been made on how to improve people's understanding of stocks and flows and many interventions that have been designed for such a purpose have not been successful.…”
Section: Introductionmentioning
confidence: 99%